2017
DOI: 10.1016/j.cub.2017.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Profound reversible seasonal changes of individual skull size in a mammal

Abstract: Due to an author oversight at the proof stage, this article was published online and in print with a typo on page R1106, where we stated that ''we measured braincase height (BCH), skull length (SKL) and braincase weight (BCW).'' This should have read ''we measured braincase height (BCH), skull length (SKL) and braincase width (BCW).'' The article has now been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A recent study by Lazaro et al . () looked at the variation in terms of body and braincase sizes in relation to seasons in shrews ( Sorex araneus ). They found that there was a decrease in body mass just before the winter (17.6%) and then a dramatic increase of 83.4% in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lazaro et al . () looked at the variation in terms of body and braincase sizes in relation to seasons in shrews ( Sorex araneus ). They found that there was a decrease in body mass just before the winter (17.6%) and then a dramatic increase of 83.4% in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…First, they have basal metabolic rates of, on average, more than 300% of those predicted for non‐shrew mammals of their size, as well as greater average body temperatures than other shrews (Taylor, ). As a result of these high metabolic demands, Sorex shrews need to feed at least every few hours (Churchfield, ) and their body mass drops significantly in the winter (including reduction in brain size; Dehnel, ; Pucek, ; Lázaro, Dechmann, LaPoint, Wikelski, & Hertel, ). Second, unlike many other cold‐adapted mammals, Sorex shrews are not known to hibernate or use torpor in the winter (Taylor, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of a full annual cycle, animals may change their foraging behavior (Dearing ), diet (Nadjafzadeh et al ), movement strategies (Newton ), space use (Sumasgunter et al ), energy budget (Czenze et al ), gonad size and sexual behavior (Gill ), and brain size, cranial morphology, and metabolic rate (Lázaro et al ). This variation is often driven by seasonal fluctuations in either resource availability or reproductive physiology.…”
mentioning
confidence: 99%